Device and Patient-Related Complications of Renal Denervation for Uncontrolled Hypertension: A Post-Marketing Analysis of the FDA MAUDE Database - Sai Tharun Reddy Gopannagari; Kesava Manikanta Achuta; Divya Ganisetti; Shravya Pingili; Towfiqul Chowdhury; Chadi Saad (Spartan Medical Research Journal, 2026)
Introduction Renal denervation (RDN) has re-emerged as an adjunctive therapy for uncontrolled hypertension following recent U.S. Food and Drug Administration (FDA) approvals of ultrasound- and radiofrequency-based systems. Although randomized trials report a favorable safety profile, post-marketing data may reveal additional safety signals in real-world settings. Methods We performed a retrospective descriptive observational study of reports in the FDA Manufacturer and User Facility Device Experience (MAUDE) database from inception through December 22, 2025, which represented the final date of data extraction. Reports were identified using product code “QYI” and brand names “Paradise” and “Symplicity Spyral.” Eligible reports describing RDN for hypertension management were manually reviewed and categorized as vascular, device-related, hemodynamic/arrhythmic, neurologic, or other events. Results A total of 33 reports were identified, including 19/33 (57.6%) involving the Paradise system and 14/33 (42.4%) involving the Symplicity Spyral system. Vascular complications were the most frequently reported events, accounting for 15/33 reports (45.5%), including renal artery dissection (5/33, 15.2%), thrombosis (3/33, 9.1%), vasospasm (3/33, 9.1%), pseudoaneurysm (2/33, 6.1%), renal hematoma (1/33, 3.0%), and acute limb ischemia (1/33, 3.0%). Device-related events accounted for 10/33 reports (30.3%), most commonly expired catheter use (4/33, 12.1%) and catheter or component malfunction (6/33, 18.2%). Hemodynamic/arrhythmic events occurred in 4/33 reports (12.1%), neurologic events in 2/33 (6.1%), and other events accounted for 2/33 reports (6.1%). Conclusions In this descriptive MAUDE analysis, RDN was associated with uncommon but clinically relevant vascular and device-related adverse events in real-world practice. These findings support continued post-marketing surveillance as use of RDN expands. Interpretation is limited by the passive nature of MAUDE reporting, including underreporting, incomplete data, and the inability to determine incidence or causality.